Social Responsibility: Can it Contribute for Sustainable Welfarism? - Tiwari, Indra P. (Journal of Development and Social Engineering, 2017)
Human beings as natural persons as well as other juristic persons are expected to contribute to the society as part of social responsibility in addition to their defined legal and professional responsibilities with a view to continuously building a better and equally equitable, peaceful and sustainable society. If defined “social responsibility” as the voluntary contribution of the juristic and natural persons, i.e. government, corporations/ companies, organizations/ associations, and individual human beings, should the matter of contributing for the betterment of the society through social responsibility be left to the contributor? Contrarily, in a situation of functioning within the stringent laws, rules and regulation of the Government by all juristic and natural persons, should we expect something more than their legal and main responsibilities from them on the name of social responsibilities? Do society, moreover communities and individuals, expect special/additional social responsibilities from all persons, and if so, what sorts of responsibilities are included with what priorities? Similarly, are there different approaches in defining responsibilities of various persons, juristic and natural? If yes, in what situations and what conditions? Debates are going on about the functions and procedures for undertaking social responsibilities as well. This paper in the above context is discussing the objectives and missions, functions, structure(s), processes, the expectations from social responsibilities fulfilled and unfulfilled, and the impacts in the society as expected and not expected, thereby open up the areas for comprehensive and holistic discussion.